Bioaccumulation and trophic magnification of short chain chlorinated paraffins in marine organisms from East China Sea. (December 2021) - Hu, Hongmei; Qu, Jianli; Zhao, Meirong; Wu, Pengfei; Zhu, Wenbin; Zhou, Yongdong; Jin, Hangbiao
Abstract: As new persistent organic pollutants, short chain chlorinated paraffins (SCCPs) have recently received particular attention. However, knowledge on their bioaccumulation and trophic magnification in marine organisms from East China Sea (ECS) is still scare. In this study, we investigated the concentrations of SCCPs in seawater ( n  = 15) and marine organisms ( n  = 88) collected from ECS. The total concentrations of SCCPs (∑SCCPs) ranged from 12.5 to 242 ng/L in seawater and from 12.8 to 1819 ng/g wet weight (ww) in organisms. C10–11 SCCPs and Cl5–7 SCCPs were the predominant homologues in all samples, with the mean proportions of 70 ± 6.5% and 80 ± 7.8% in seawater, as well as 52–77% and 61–84% in marine organisms, respectively. The logarithm bioaccumulation factor (log BAF) values of ∑SCCPs were in the range of 2.04–3.79 in zooplankton, fish, shrimp, crab, shellfish, snail, and cephalopod. The log BAF values of SCCP homologues (1.33–4.75) increased significantly with the increase of their logarithm octanol–water partition coefficients (log K OW ) values, indicating that hydrophobicity is the major factor controlling the bioaccumulation of SCCPs. The trophic magnification factor (TMF) value of ∑SCCPs was calculated to be 3.98, indicating the potential trophic magnification of SCCPs in this marine food web from ECS. A slightly increasing trend was observed between the TMF values of SCCP homologues and their log K OW values. Overall, for the first time, this study systematically examined the bioaccumulation and trophic magnification of SCCPs in the marine food web from East China Sea. Graphical abstract: Unlabelled Image Highlights: Occurrence of SCCPs in marine organisms from ECS was first investigated. C10–11 SCCPs and Cl5–7 SCCPs were the predominant homologues in all samples. Significant correlations were found between logBAFs and log K OW values. Trophic magnification of SCCPs was observed in marine food web.